2016
DOI: 10.1016/j.jnucmat.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria in the U-Si system from first-principles calculations

Abstract: Density functional theory calculations have been used with spin-orbit coupling and onsite Coulomb correction (GGA+U) methods to investigate the U-Si system. Structural prediction methods were employed to identify alternate stable structures. Convex hulls of the U-Si system were constructed for each of the methods to highlight the competing energetics of various phases. For GGA calculations, new structures are predicted to be dynamically stable, but these have not been experimentally observed. When the GGA+U (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 68 publications
7
38
0
1
Order By: Relevance
“…The negative Hall coefficient together with positive Seebeck coefficient, indicate that a simple free electron model cannot be used to describe the electronic properties of this system. DFT calculations using spin-orbit coupling and an on-site coulomb correction [31] [32] indicate that besides uranium 5f-electrons there are also several overlapping states, in particular 6d and 3p at the Fermi level. Interplay between conventional and extraordinary components with differing electron-like or hole-like character could lead to anomalous values for RH [33].…”
Section: Seebeck and Hall Effectmentioning
confidence: 99%
“…The negative Hall coefficient together with positive Seebeck coefficient, indicate that a simple free electron model cannot be used to describe the electronic properties of this system. DFT calculations using spin-orbit coupling and an on-site coulomb correction [31] [32] indicate that besides uranium 5f-electrons there are also several overlapping states, in particular 6d and 3p at the Fermi level. Interplay between conventional and extraordinary components with differing electron-like or hole-like character could lead to anomalous values for RH [33].…”
Section: Seebeck and Hall Effectmentioning
confidence: 99%
“…practically, this small energy could be negated by entropic effects or small variations in the 164 energy associated with the methods [19]. Despite the small energy, as the reaction is predicted 165 to be favourable this phase will be considered to judge the potential deviation in stoichiometry 166 for U 3 Si 2 in the presence of U 5 Si 4 .…”
Section: Excess Si From Usi: 106mentioning
confidence: 99%
“…Recent theoretical work by Noordhoek et al [18] has been carried out to identify a reliable 68 method to simulate U-Si compounds. It was shown that the use of an on-site Coulombic 69 correction (GGA+U) method [19] was vital to predict the experimentally observed phases as 70 structurally and thermodynamically stable. A +U value of 1.5eV was suggested as appropriate 71…”
mentioning
confidence: 99%
“…The work on silicide [19][20][21][22] or carbide 23 is only starting but the work on oxide fuels has already received many contributions. It is outside the scope here to mention all of them, but Xe has been studied in U O 2 24 , other actinide oxide fuels 25 , and its diffusion following complex paths has also been investigated 26 , as well as the effect of nonstoichiometry and irradiation conditions on its diffusion properties 27 .However, krypton has never been considered in such works either for UN, except when swelling was the sole phenomenon being investigated 17 .…”
Section: Introductionmentioning
confidence: 99%